TECHNOLOGY AND THEIR PACKAGING - Abdurahmonov , Lazokat Abduvohid qizi (Educational Research in Universal Sciences, 2023)
To prevent wastage of fruits, three fruits are processed and dried. It should be dried in a condition that meets the requirements for drying. The selection of packaging containers for dried products is explained in our article.